The Effect of Small Games on Motivation to Participate in Physical Education - Sulistyo, Yully Wahyu; Nenggar, Aditya Harja (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
This study aims to determine the influence of small games on motivation in participating in PJOK learning. This research method uses pseudo-experiments. The sample was taken from 34 learners. The sampling technique uses cluster random sampling. Instruments used to measure student motivation using questionnaires. The data analysis technique used is the T-test (paired test)h, calculated with the help of SPSS 27. Based on the data that has been calculated, the result of the calculated t-value is 4.5467. In contrast, the probability value (sig) = 0.00 can be seen that the probability (sig) of 0.00 < 0.05, then H0 is processed, and H1 is accepted. This means that small games significantly influence motivation in participating in PJOK learning. Recommendations for future research researchers include developing game models that can increase motivation and other variables in PJOK learning so that learning objectives can be achieved.